GAMBARAN TINGKAT KEGAWAT DARURATAN PASIEN DI INSTALASI GAWAT DARURAT (IGD) RUMAH SAKIT BHAYANGKARA KOTA MANADO - Sahensolar, Livnie Nansi; Bidjuni, Hendro; Kallo, Vandri (JURNAL KEPERAWATAN, 2021)
Abstract: Background in this research, namely a State of emergency is situation that requires the handling or action immediately to eliminate the treat life of the victim. The research of aim is to know the Description of the level of emergency patients in the Emergency Room (ER) Hospital Bhayangkara Manado City. The Method is using descriptive research. Sample in this research amounted to 100 respondents obtained through medical record with the research instrument used is in the form of observation sheet which consists of the priority handling of patients is to determine priority I and Priority II. The results of the research, the characteristics based on the age of the response and the most on the age of The Elderly the Beginning of 46-55 years with a total of 24 respondents (24%), characteristics based on the gender of largest in the male gender with a total of 54 respondents (54%), characteristics based on the medical diagnosis most are on the medical diagnosis of Dyspepsia with the number 47 diagnosis (47%), and based on Emergency patients are on Emergency priority of yellow with the amount of 62 respondents (62%). Conclusion, Patients who come to the emergency room with emergency patients with Priority triage shows the most Priority Triage yellow.Keywords : Dyspepsia; Emergency Room; Priority of the Patient; Rate of Emergency Patients; TriageAbstrak: Latar Belakang penelitian yaitu Keadaan gawat darurat merupakan keadaan yang memerlukan penanganan atau tindakan segera untuk menghilangkan ancaman nyawa korban. Tujuan penelitian untuk mengetahui Gambaran tingkat kegawat daruratan pasien di Instalasi Gawat Darurat (IGD) Rumah Sakit Bhayangkara Kota Manado. Metode Penelitian ini menggunakan penelitian deskriptif. Sampel, pada penelitian ini berjumlah 100 responden yang diperoleh melalui rekam medis dengan instrument penelitian yang digunakan yaitu dalam bentuk lembar oservasi yang terdiri dari prioritas penanganan pasien yaitu untuk menentukan prioritas I dan Prioritas II. Hasil penelitian, karakteristik berdasarkan umur respon dan terbanyak pada umur Masa Lansia Awal 46-55 tahun dengan jumlah 24 responden (24%), karakteristik berdasarkan jenis kelamin terbanyak pada jenis kelamin laki-laki dengan jumlah 54 responden (54%), karakteristik berdasarkan diagnose medis terbanyak berada pada diagnose medis Dysepsia dengan jumlah 47 diagnose (47%), dan berdasarkan kegawat daruratan pasien terbanyak berada pada kegawat daruratan prioritas kuning dengan jumlah 62 responden (62%). Kesimpulan, Pasien yang datang ke Instalasi gawat darurat dengan kegawat daruratan pasien dengan Prioritas triase menunjukan sebagian besar Prioritas Triase kuning.Kata Kunci : Dispepsia; Instalasi Gawat Darurat; Prioritas Pasien; Tingkat Kegawat daruratan Pasien; Triase